Why managers hold shares of their firm: An empirical analysis - Ulf von Lilienfeld-Toal; Stefan Ruenzi (University of Cologne, Centre for Financial Research (CFR), 2006)
We examine the relationship between CEO ownership and stock market performance of S&P 500 (S&P 1500) firms from 1994-2005 (1996-2005). We find that firms in which the CEO holds a considerable share of outstanding stocks outperform the market by up to 16% p.a. after controlling for traditional risk factors like size, book-to-market and momentum. This offers an explanation why so many CEOs hold a large fraction of their own company's stocks. They do so simply because it pays. We also examine several potential explanations why the existence of an owner CEO is not fully priced but leads to abnormal returns.
Keywords: G12; G30; 330; CEO-Ownership; Asset Pricing with large shareholders